"I was always struggling": Caregivers' experiences of transitioning a child from oral to long‐term non‐oral feeding at an out‐patient hospital clinic in South Africa. (24th May 2021) - Neille, Joanne; Selikson, Gabriella
Abstract: Background: As the prevalence of paediatric dysphagia increases, the need for long‐term non‐oral feeding has also increased. Despite these developments, little is known about caregiver experiences of transitioning a child onto long‐term non‐oral feeds, and the factors which influence the process of decision‐making and the provision of consent to do so. This paper aims to explore these factors. Methods: Semi‐structured interviews were conducted with nine participants recruited from the multidisciplinary out‐patient non‐oral feeding clinic at a hospital. Interviews explored caregiver experiences of decision‐making and the process of providing consent when transitioning their child to non‐oral feeds, as well as the support structures available to the caregivers. Interviews were audio recorded and transcribed, then analyzed using thematic analysis (Braun & Clarke, 2013) and content analysis (Neuendorf, 2016). Results: Challenges to care and quality of life, access to information and culturally relevant counselling, and the involvement of family members and significant others emerged as prominent themes. Findings suggest that quality of life was the most common motivating factor for transitioning a child to non‐oral feeding methods. Several participants suggested that support and information sharing via digital platforms were both useful and effective. Implications: The findings highlight caregivers' needs for improved access to information and social support. The findings hold implications for training of healthcare providers working in similar contexts and for models of service delivery which ensure that family‐centred intervention can be delivered in culturally and contextually relevant ways. With widespread access to smartphones, counselling should include digital messaging as a way of providing support and information sharing. Future research should focus on the complexities of counselling and the process of informed consent in settings impacted by diverse cultural, contextual and linguistic barriers, as well as the potential value of mobile health (mhealth) in ensuring improved health outcomes.